THE RISKS OF PERSONAL DATA THEFT IN FINTECH-BASED ONLINE LOAN APPLICATIONS DUE TO THE ABSENCE OF LAW IN INDONESIA - Devianti, Dwi Nugrahayu; Djatmika, Prija; Sukarmi, Sukarmi (Jurisdictie: Jurnal Hukum dan Syariah, 2020)
The online loan via financial technology (fintech) is currently a new buzz in Indonesian society. Its facilities and ease in proposing the loan are very much attracting. However, this online loan practice often raises legal issues; one of them is personal data misuse. This article analyzes the usage of other people’s personal data in fintech services. This is a doctrinal legal research with statute approach. The results reveal that personal data protection has yet firmly ruled in legislation. This proves that privacy is not an urgent matter to safeguard. It then implies to the many cases on personal data theft in online loan. The operators of fintech services are responsible to protect customers’ personal data. Those found guilty to misuse the personal data will be subject to criminal sanction.Pinjaman online melalui teknologi finansial menjadi trend baru masyarakat Indonesia. Berbagai fasilitas dan kemudahan dalam pengajuan pinjaman menjadi daya tarik tersendiri. Namun, praktik pinjaman online sering menimbulkan persoalan hukum, salah satunya adalah penyalahgunaan data pribadi. Artikel ini bertujuan menganalisis penggunaan data pribadi orang lain dalam layanan finansial teknologi. Artikel ini berasal dari penelitian hukum doctrinal dengan pendekatan peraturan perundang-undangan. Hasil penelitian ini menunjukkan bahwa perlindungan data pribadi belum diatur secara tegas dalam peraturan perundang-undangan. Kondisi ini menunjukkan bahwa privasi bukan persoalan yang urgen untuk dilindungi. Hal ini berimplikasi terhadap maraknya pencurian data pribadi dalam pinjaman online. Penyelenggara jasa layanan finansial teknologi memiliki tanggung jawab untuk melindungi data pribadi nasabah. Penyelenggara yang terbukti menyalahgunakan data pribadi dapat dikenai sanksi pidana.